1990
DOI: 10.1200/jco.1990.8.4.638
|View full text |Cite
|
Sign up to set email alerts
|

Autologous marrow transplantation for malignant lymphoma: a report of 101 cases from Seattle.

Abstract: Between October 1979 and January 1988, 101 patients with malignant lymphoma who failed initial induction treatment or relapsed received high-dose combination chemotherapy or chemoradiotherapy followed by infusion of autologous bone marrow. Twenty-eight of the 101 patients survive, 18 of whom are disease-free for a median of 26 (range, 12 to 66) months. The 5-year actuarial probabilities of survival, event-free survival (EFS), and relapse from transplantation were 20%, 11%, and 84%, respectively. Multivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(73 citation statements)
references
References 7 publications
2
70
0
1
Order By: Relevance
“…5,7 Resolution of these issues is complicated by the fact that only limited data are available. [5][6][7][8][9][10][11][12][13][14] Additionally, many studies of high-dose therapy and transplantation in low-grade NHL have included cases of mixed cell follicular NHL, 5,11 a disorder which may not be a classical low-grade lymphoma. [15][16][17] To clarify the role of high-dose therapy in conjunction with stem cell transplantation, this report summarizes our results using autologous or allogeneic bone marrow or stem cell transplantation in patients with follicular small cleaved cell lymphoma (SCCL).…”
mentioning
confidence: 99%
“…5,7 Resolution of these issues is complicated by the fact that only limited data are available. [5][6][7][8][9][10][11][12][13][14] Additionally, many studies of high-dose therapy and transplantation in low-grade NHL have included cases of mixed cell follicular NHL, 5,11 a disorder which may not be a classical low-grade lymphoma. [15][16][17] To clarify the role of high-dose therapy in conjunction with stem cell transplantation, this report summarizes our results using autologous or allogeneic bone marrow or stem cell transplantation in patients with follicular small cleaved cell lymphoma (SCCL).…”
mentioning
confidence: 99%
“…The methods of pretransplant conditioning and posttransplant care have been described [21,22]. Allogeneic transplant recipients were given cyclosporine plus a short course of methotrexate as GVHD prophylaxis [20].…”
Section: Methodsmentioning
confidence: 99%
“…These patients have a poor prognosis, even with autoSCT, [46][47][48][49] although recently a number of groups have demonstrated that autoSCT can effectively salvage about 50% of patients sensitive to second-line chemotherapy. [50][51][52] Preliminary data suggest that alloSCT may be effective for patients with induction failure, 19,31 although the effect of chemosensitivity has not been formally assessed in this population.…”
Section: When To Transplant?mentioning
confidence: 99%